2 `-5 `-Isomerically linked thrombin-binding aptamer (isoTBA) forms a stable unimolecular parallel G-quadruplex in the presence of Sr2+ Ions - Wagh, Atish A.; Fernandes, Moneesha (ChemistrySelect, 2019)
The ability of the isomeri 2 `-5 `-phosphodiester-linked thrombin-binding DNA aptamer pentadecamer G(2)T(2)G(2)TGTG(2)T(2)G(2) (isoTBA), to fold into G-quadruplex structures in the presence of different mono- and divalent cations is reported. Strikingly, Sr2+ ions cause isoTBA to fold into a stable parallel unimolecular G-quadruplex, in contrast to the antiparallel unimolecular G-quadruplex fold observed in the presence of K+. IsoTBA being advantageously more stable than TBA to nuclease degradation, may thus be useful in the selective detection of Sr2+ ions, which it can sense with a detection limit of similar to 55 mu M.
Keywords: 2 `-5 `-phosphodiester; parallel DNA G-quadruplex; strontium binding; thrombin-binding aptamer; unimolecular G-quadruplex